Os Centros Educacionais Unificados (CEUs) da Prefeitura Municipal de São Paulo e o rendimento escolar dos alunos - Barberi, Fabíola Francisco (2012)
This research aimed at verifying what were the indexes of school performance presented by the students of the Unified Educational Centres (known in Portuguese as CEUs) during the years 2005, 2007 and 2009, according to Prova Brasil (Brazil Test), by comparing them, in one hand, with the performance indexes of the country and São Paulo´s municipal network, and in other hand, by comparing them with the same indexes among the Unified Educational Centres units by geographic location and the social exclusion indexes of its surroundings. The main question that guided this study was defined this way: do the differenced architectural project and all the resources offered by the Unified Educational Centres reflect on the improvement of the students´ school performance in Portuguese and Math? The methodological procedure adopted consisted on a documental research that included: legislation study about the Unified Educational Centres, statements that guided its implantation, regiment, productions related to the Centres and analysis of scholars linked to the theme. For the analysis of school performance in Portuguese and Math the instrument used was Prova Brasil. Among others are: Viñao Frago, Escolano (2001), Gimeno Sacristan (1999) and Apple (2001) who theoretically fundamented the research. After the analysis of Prova Brasil it was found that the Unified Educational Centres presents an inferior performance compared to the schools of São Paulo´s municipal network and Brazilian schools and the high exclusion index does not negatively influence theperformance of students and the Unified Educational Centre forms an educational innovation